(untitled) (Dhaka University Journal of Science, 2015)
The results presented in this study examined factors associated with antenatal care seeking behaviour using the data of BDHS-2007. Multivariate techniques were applied to identify significant determinant of ANC utilization by women in Bangladesh. Five factors have been determined by using factor analyses and these factors are considered as underlying reasons behind ANC seeking behaviour. One of these factors is biological and the remaining ones are socio-economical. Linear discriminant analysis explained the competence of factors identified in this study. These five factors are considered accurate for approximately 70 percent of the observations. It is expected that the results presented in this study will help to formulate better policies and program interventions to enhance the ANC seeking behaviour of women in Bangladesh. DOI: http://dx.doi.org/10.3329/dujs.v63i1.21762 Dhaka Univ. J. Sci. 63(1): 19-23, 2015 (January)